Usefulness of Heart Rate at Rest as a Predictor of Mortality, Hospitalization for Heart Failure, Myocardial Infarction, and Stroke in Patients With Stable Coronary Heart Disease (Data from the Treating to New Targets [TNT] Trial) - Ho, Jennifer E.; Bittner, Vera; DeMicco, David A.; Breazna, Andrei; Deedwania, Prakash C.; Waters, David D. (The American journal of cardiology, 2010)
The heart rate at rest (HR) is a predictor of cardiovascular (CV) mortality. However, its effect on nonfatal CV events is unknown. The aim of the present post hoc analysis of the Treating New Targets (TNT) trial was to assess the effect of the HR at rest on major CV events in patients with stable coronary heart disease. A total of 9,580 subjects were included in the present analysis and were followed up for a median of 4.9 years. The rate of major CV events was 11.9% in those with a baseline HR of ≥70 beats/min versus 8.8% in those with a baseline HR of <70 beats/min. An increased HR at rest was associated with CV events, even after adjustment for differences in baseline characteristics (unadjusted hazard ratio 1.16 for every 10-beats/min increase, 95% confidence interval [CI] 1.10 to 1.23, p <0.0001; adjusted hazard ratio 1.08 per 10-beats/min increase, 95% CI 1.02 to 1.16, p = 0.018). A HR ≥70 beats/min was a significant independent predictor of all-cause mortality (hazard ratio 1.40, 95% CI 1.14 to 1.71, p = 0.001) and heart failure hospitalization (hazard ratio 2.30, 95% CI 1.80 to 2.95, p ≥0.0001). However, this association was not observed for stroke or myocardial infarction (p = 0.11 and p = 0.68, respectively). In conclusion, in patients with stable coronary heart disease, every 10-beats/min increase in the HR at rest was associated with an 8% increase in major CV events. In particular, a HR at rest of ≥70 beats/min was associated with a 40% increased risk of all-cause mortality and more than doubled the risk of heart failure hospitalization, but not the risk of stroke or myocardial infarction.